Wheat, barley, and oat silages for beef cattle - Bolsen, K.; Oltjen, J. (Kansas State University. Agricultural Experiment Station, 2011)
Wheat, barley, or oat silages can provide excellent alternatives to corn and sorghum silages for beef cattle. Wheat, barley, oat, and corn silages were fed to steers in seven trials for the past five years (Prog. Rpt. 210, 230, 262 and 291, Kansas Agr. Expt. Sta.). The forages were whole plant and had been harvested in the dough state except as indicated. Silage was made in concrete silos (10 x 50 feet). When necessary, water was added to provide a moisture content of at least 60% in the ensiled forage. Cereal silage varieties included soft red winter, awnless wheats, Blue Boy, Blue Boy II, and Arthur, hard red winter, awned wheats, Parker, Eagle and Sage; winter, awned barleys, Paoli and Kanby, and spring oats, Trio and Loci.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Wheat; Barley; Oats